ON THE PEDAGOGICAL CHARACTERISTICS OF THE TRAINING PROCESS IN FOREIGN MILITARY EDUCATIONAL INSTITUTIONS - Eshmuradov Z.M. (Scholars Digest Publishing, 2023)
This article is devoted to such an urgent issue as the study, generalization and analysis of the pedagogical characteristics of the learning process in the military educational institutions of states in the post-soviet space, as well as the extraction of the most positive experience from it for further implementation in the educational process of national higher military educational institutions and all-round development of their teaching staff.
Keywords: military educational institutions, military specialists, teacher, trainees, educational process, innovative teaching, cognitive activity, concepts, methods.